Characterization of SARS-CoV-2 Variants N501Y.V1 and N501Y.V2 Spike on Viral Infectivity - Tang, Haijun; Gao, Long; Wu, Zhao; Meng, Fang; Zhao, Xin; Shao, Yun; Shi, Xiaohua; Qiao, Shigang; An, Jianzhong; Du, Xiaohong; Qin, F. Xiao-Feng (Frontiers in Cellular and Infection Microbiology, 2021)
SARS-coronavirus 2 (SARS-CoV-2), pathogen of coronavirus disease 2019 (COVID-19), continues to evolve to adapt to the host and evade antiviral immunity. The newly emerging variants N501Y.V1 (B.1.1.7) and N501Y.V2 (B.1.351) lineages, first reported in the United Kingdom and South Africa respectively, raised concerns due to the unusually rapid global spread. The mutations in spike (S) protein may change the transmission properties and biological characteristics, and contribute to the rapid spread of these virus. Here, with a vesicular stomatitis virus (VSV) pseudotype system, we demonstrated that the pseudovirus with 501Y.V2 lineage S mutation (K417N, E484K, N501Y and D614G) has higher infection efficiency than pseudovirus with wildtype (WT) and D614G S protein. Moreover, pseudovirus with N501Y.V1 (69-70 deletion, 144 deletion, N501Y, A570D, D614G, P681H, T716I, S982A and D1118H) and N501Y.V2 S protein has better thermal stability than WT and D614G, suggesting that these mutations may increase the stability of SARS-CoV-2 S protein and virion. However, the pseudovirus with N501Y.V1 and N501Y.V2 S protein have similar sensitivities to inhibitors of protease and endocytosis with WT and D614G. These findings could be of value in the prevention of the spread of virus and development of drugs for emerging SARS-CoV-2 variants.